2017
DOI: 10.7573/dic.212298
|View full text |Cite
|
Sign up to set email alerts
|

NEPA, a new fixed combination of netupitant and palonosetron, is a cost-effective intervention for the prevention of chemotherapy-induced nausea and vomiting in the UK

Abstract: BackgroundThe objective was to evaluate the cost-effectiveness of NEPA, an oral fixed combination netupitant (NETU, 300 mg) and palonosetron (PA, 0.5 mg) compared with aprepitant and palonosetron (APPA) or palonosetron (PA) alone, to prevent chemotherapy-induced nausea and vomiting (CINV) in patients undergoing treatment with highly or moderately emetogenic chemotherapy (HEC or MEC) in the UK.ScopeA systematic literature review and meta-analysis were undertaken to compare NEPA with currently recommended anti-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Ten of the 13 economic studies included data of clinical outcomes from randomized controlled trials. The clinical data of Chanthawong et al ( 22 ) and Cawston et al ( 20 ) came from systematic review and metaanalysis. Nakamura et al ( 27 ) acquired data from a retrospective analysis of direct medical costs of National Hospital Organization Nagoya Medical Center between January 2009 and December 2013.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of the 13 economic studies included data of clinical outcomes from randomized controlled trials. The clinical data of Chanthawong et al ( 22 ) and Cawston et al ( 20 ) came from systematic review and metaanalysis. Nakamura et al ( 27 ) acquired data from a retrospective analysis of direct medical costs of National Hospital Organization Nagoya Medical Center between January 2009 and December 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 studies included, eight of used the decision analytical model ( 18 , 21 25 , 28 , 30 ), four used the Markov model ( 19 , 20 , 26 , 29 ), and one study did not use model analysis ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to all four comparator regimens, NEPA resulted in decreased incremental medical cost (€30-€71) and increased incremental QALDs (0.08-0.26) in HEC patients [32]. Similarly, from a British healthcare perspective, NEPA was the dominant strategy in HEC patients, resulting in a reduction of costs and a gain of QALDs versus APR + PALO [20]. The results are also consistent with the finding-noted within the National Comprehensive Cancer Network (NCCN) guidelines for antiemesis [8]-that netupitant is effective at decreasing delayed nausea.…”
Section: Discussionmentioning
confidence: 95%
“…Utilities of 0.90, 0.70, and 0.24 were assigned for the outcomes of CP, CR, and IR, respectively, consistent with previously published economic models for CINV [20,21]. Quality-adjusted life-days (QALDs) were calculated by summing the patient's quality-adjusted time over the 5-day trial; given the average age and disease burden, the maximum possible QALDs (i.e., having no CINV) for the period was 4.5 (i.e., 0.90 × 5 days).…”
Section: Utilitiesmentioning
confidence: 93%
“…Cawston et al reported the cost-effectiveness of a combination drug (NEPA: netupitant plus palonosetron), comparing the combination with APR and PALO using a Markov model in the UK medical care system. They reported that NEPA was cost-effective for preventing CINV associated with highly or moderately emetogenic chemotherapy in the UK [27]. Restelli et al reported the cost-effectiveness of NEPA, comparing the combination with NK1-RA (APR or fosaprepitant) and 5-HT3RA (PALO or ondansetron) in patients receiving highly or moderately emetogenic chemotherapy using a Markov model in the Italian medical care system.…”
Section: Discussionmentioning
confidence: 99%